ANALISIS FINANSIAL USAHA KERUPUK IKAN GABUS (Channa striata) DI KELURAHAN KOTA BANGUN ULU KECAMATAN KOTA BANGUN KABUPATEN KUTAI KARTANEGARA - Hendrieco Dwintara Teguh Pramuda; Gusti Haqiqiansyah; Juliani (Jurnal Pembangunan Perikanan dan Agribisnis, 2016)
The purpose of this research is to analyze the financial feasibility of Fish Cracker Cork businesses based on the criteria of investment that namely, the NPV (Net Present Value), IRR (Internal Rate of Return), Net B/C (Net Benefit Cost Ratio), PP (Payback Period), knowing then current marketing and the factors that affect the business of fish crackers Cork. The Result showed that the business of fish crackers Cork in Kota Bangun Ulu districk, Kutai Kartanegara for the financially viable and prospective to operable and developed, evidenced by the value of the investment criteria i.e. NPV = Rp.102.125.320,82; IRR = 313%; Net B/C = 11.76 and PP = 5.10 month. These result indicate that fish crackers Cork business result can give you an advantage, since before the end of venture investment model, already issued can be restored. Fish Crackers Cork produced by communities in the citizens of the Kota Bangun Ulu and the marketing are samarinda, Tenggarong Subdistrict around Kota Bangun. The Factors that influence are a factor of nature, the season, the factor of technology and skill as well as experience.